1995
DOI: 10.1097/00005392-199511000-00047
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Varicocelectomy on Serum Testosterone Levels in Infertile Men with Varicoceles

Abstract: Varicocelectomy can increase serum testosterone for infertile men with varicoceles. Although improvement in serum testosterone does not necessarily cause a direct improvement in semen quality, varicocelectomy may improve hormonal and spermatogenic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 11 publications
4
55
1
4
Order By: Relevance
“…Deleterious effects of altered Leydig cell function and seminiferous tubule damage in varicocele patients can disrupt the endocrine pathway affecting follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone [Pasqualotto et al 2005;Weiss et al 1978]. On one hand a study has indicated that varicocelectomy improved Sertoli cell and Leydig cell function increasing serum testosterone, and resulted in improvement in sperm concentration and motility [Su et al 1995]. On the other hand other groups have shown that there was no statistically significant change after the operation in levels in the semen of FSH, LH, and testosterone [Fujisawa et al 1994;Segenreich et al 1986].…”
Section: Discussionmentioning
confidence: 99%
“…Deleterious effects of altered Leydig cell function and seminiferous tubule damage in varicocele patients can disrupt the endocrine pathway affecting follicle-stimulating hormone (FSH), luteinizing hormone (LH), and testosterone [Pasqualotto et al 2005;Weiss et al 1978]. On one hand a study has indicated that varicocelectomy improved Sertoli cell and Leydig cell function increasing serum testosterone, and resulted in improvement in sperm concentration and motility [Su et al 1995]. On the other hand other groups have shown that there was no statistically significant change after the operation in levels in the semen of FSH, LH, and testosterone [Fujisawa et al 1994;Segenreich et al 1986].…”
Section: Discussionmentioning
confidence: 99%
“…Such cases usually father a child 5-6 months after surgery. [1,3,6,9,10] O'Brien et al [4] reported that adult varicocelectomy resulted in signiÞ cant improvement in semen quality and pregnancy outcome. Following surgery, majority of varicocele cases show improvement in semen parameters, DNA integrity, testosterone levels and testicular volume.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] Increased venous and adrenal reflux affects testicular microvasculature by down-regulating the arterial inflow, and precapillary vasoconstriction affects nutrient supply to testis and also adversely affects mitochondrial oxidative phosphorylation. [10] Varicocele adversely affects Leydig cell function, leading to decreased testosterone production and increased estrogen levels. [8,9,11] T e s t o s t e r o n e i s r e q u i r e d f o r o p t i m a l spermatogenesis, and reduced levels may lead to hypospermatogenesis.…”
mentioning
confidence: 99%
“…30 A varicocele is associated with bilateral spermatogenic abnormalities and Leydig cell dysfunction. [31][32][33][34][35] The testicular histology in infertile men with varicocele is variable, but most studies report reduced spermatogenesis (hypospermatogenesis). The observed increase in germ cell apoptosis is thought to occur as a result of hyperthermia and low testosterone levels in the testicle.…”
Section: Pathophysiology Of Varicocelementioning
confidence: 99%